MOTIV ASI BELAJAR BAHASA INGGRIS PADA SISWA SEKOLAH MENENGAH PERTAMA DALAM MENGHADAPI UJIAN NASIONAL DITINJAU DARI DUKUNGAN SOSIAL ORANG TUA DAN KOMPETENSI GURU - Sukodoyo Sukodoyo; A. Rachmad Djati W; Praharesti Eriany (PSIKODIMENSIA, 2013)
The purpose of this research is to test empirically the correlation between parental social support, teacher competency and learning English motivation of junior high school students in facing national examination. Subjects were 133 students of 9th grade in SMP Negeri I Getasan, Subdistrict Getasan, Semarang Regency. Learning Motivation scale, Parental Social Support scale, and Teacher Competency scale were used to collect data. Regression Analysis showed R = 0,508 (p